Tingkat Kebugaran Jasmani Mahasiswa Program Studi Pendidikan Guru Sekolah Dasar STKIP PGRI Bandar Lampung - Anindito, Filardi (STKIP PGRI Bandar Lampung, 2022)
The level of physical fitness of PGSD STKIP PGRI Bandar Lampung students class of 2020. The research aims to determine the level of physical fitness of students of PGSD STKIP PGRI Bandar Lampung study program class of 2020. This study used descriptive research. The population of this study were students of the 2020 Elementary School Teacher Education (PGSD) study program at STKIP PGRI Bandar Lampung, totaling 116 students. The sampling technique used was total sampling or saturated sampling, the sample size used was 116 students. This study used the instrument used to collect data, namely a multi-stage physical fitness test or what is often called the Beep Test according to Kenneth H Copper. Research data were analyzed using frequency distribution and tabulation. Based on the results in this study, it was found that the physical fitness possessed by PGSD STKIP PGRI Bandar Lampung students was physical fitness which was said to be lacking in the amount of 84 people with a percentage of 74%, lacking in the number of 23 people with a percentage of 20%, while the number of 8 people with a percentage 7%, good with 1 person with a percentage of 1% and very good 0 people with a percentage of 0%. In general, physical fitness can be said to be lacking with the number of respondents and with that percentage. Besides that, there are also things that influence, namely external and internal factors. The environment and consistency in exercising are internal factors, while a healthy lifestyle and habits are internal factors. Suggestions that can be given in this study are to provide cognitive knowledge about the importance of exercising to maintain physical fitness 2. Provide programs for students and provide sports training 3. Familiarize students with healthy living behaviors